Mitigating anode/electrolyte interfacial Ni diffusion by a microwave sintering method for proton-conducing solid oxide fuel cells - Zhaolin Liu; Shoufu Yu; Meng Wang; Yueyuan Gu; Lei Bi (Electrochemistry Communications, 2023)
Although Ni-based anodes are commonly employed in proton-conducting solid oxide fuel cells (H-SOFCs), interfacial diffusion of Ni from the anode to the electrolyte is difficult to avoid, resulting in lower electrolyte and fuel cell performance. In this study, the electrolyte/anode half-cells are co-sintered using a microwave sintering process, providing a lower co-sintering temperature than the standard sintering approach. The lower co-sintering temperature minimizes Ba-evaporation at the electrolyte and mitigates anode/electrolyte interfacial Ni diffusion, resulting in decreased electrolyte and interfacial polarization resistance. The microwave-sintered cell outperforms the traditionally sintered cell in electrochemical performance, with higher fuel cell performance and lower cell resistances. Furthermore, the improved interfacial condition improves the fuel cell's long-term durability, allowing the cell to operate for 200 h without detectable degradation. This study presents an intriguing and simple way to reduce anode/electrolyte interfacial Ni diffusion, which improves fuel cell output and operational stability.